Localizing the Millennium Development Goals in Ghana - An Assessment of Goal 7 in the Ketu-South Municipality - Lawson, R.V. (University of Ghana, 2013)
The main objective of the study was to assess Ghana‘s progress towards localizing Millennium Development Goal (MDG) 7 on improving access to water and improved sanitary facilities with the Ketu-South Municipality as a case study. Specifically, the study sought to identify the key measures put in place by the Government of Ghana to improve access to improved water and sanitary facilities in Ketu-South, assess the institutional challenges hindering the achievement of MDG7, assess the local and environmental factors hindering the achievement of MDG 7 in the Ketu-South Municipality and lastly, to recommend contextual solutions which will support the efforts being employed towards achieving Goal 7 in Ghana. The case study design was employed in the assessment of MDG 7, Target 7c using the Ketu-South Municipality, under the qualitative approach to Social Science Research. Purposive sampling was used to select the ten (10) in-depth interview respondents. The thirty-five (35) respondents who answered the semi-structured questionnaires were conveniently sampled. The findings of the study were presented using four themes, in line with the research objectives. The study found that although the Government had made strides regarding the improvement of access to improved water sources, not much had been done in the area of improving sanitary facilities. The principal conclusion of the study was that although the government had put in place various measures to improve the access to water and sanitation, a coordination of efforts and an increased stakeholder involvement is necessary to achieve sustainability. The recommendations are that the people of Ketu-South become empowered through increased community participation. There is the need for the assembly to explore and create avenues for economic well being. In addition to the enactment of policies, government should show leadership by providing clear guidelines for implementation of policies and programmes geared toward the achievement of goal 7 in Ketu-South. This will engender the accountability of all sector players.
Thesis (MPHIL)-University of Ghana, 2013